Engrossed in the Market. Chilean Journalism in the Audiovisual Fiction Series “Bala Loca” (Chilevision, 2016 [Ensimismado en el Mercado. el Periodismo Chileno en la Serie de Ficción Audiovisual “Bala Loca” (Chilevision, 2016 - Faure-, A (Instituto de Comunicacao da NOVA, 2024)
Journalists, photographers, war correspondents, or media owners are attractive characters for audiovisual fiction. Television and streaming platforms have portrayed them as heroes or villains, as well as constructed audiovisual imaginaries about iconic cases (such as Watergate or abuses in the Catholic Church in the US) or as a cog in the wheel of power elites. However, both the production and analysis of this type of work focuses on mainstream industries, such as Hollywood or some European countries. We know less about the audiovisual portrayal of journalism in audiovisual productions for television or platforms in Latin America. The analysis of the Chilean series for free-to-air television, Bala Loca, allows us to explore the imaginaries -simultaneously complementary and contradictory- about journalism and the media in a post-dictatorial and neoliberal society. Then, this article contributes to better understanding this type of audiovisual productions in similar contexts. This reading is anchored in audiovisual and cultural studies and in qualitative methodologies focused on the production (its narratives, representations, characters, and dramatic arcs, as well as its aesthetic features) and the world of reference with which the series dialogues. At these trends’ intersection in problematizing journalism and its fictional and visual representations, this article analyzes the types of journalists and journalisms built up and rearranged within the Chilean series Bala Loca based on its communicability strategy. On one hand, its closeness and/or distance with the world it refers to; that is, Chile during the post-dictatorship from 1990 to now and how it is understood. On the other hand, it refers to the type of narrative and audiovisual resources through which these strategies are constructed. Therefore, journalism appears as heterogeneous in Bala Loca. Nonetheless, it has a strong historical referentiality, incarnates the market orientation of the profession inherited from the dictatorship (1973-1990) and illustrates the lack of public service of contemporary journalism in Chile, both in a symbolic and a material sense. © 2024 Instituto de Comunicacao da NOVA. All rights reserved.